Trik Dan Tips Pengawas Dalam Memonitoring Kinerja Guru Pendidikan Agama Kristen Selama Pandemi - Wadison Petrus; Talizaro Tafonao (Institut Agama Kristen Negeri Kupang, 2021)
This article aims to see how effective the supervisors are in monitoring Christian Religious Education teachers during the online learning process. The main problem in this paper is that supervisors need time to transform with technology so that supervisors cannot carry out supervision and guidance to teachers optimally. The method used in this study is a descriptive qualitative research method. The method used in this paper is a descriptive qualitative research method. The author obtains data through literature review, empirical data, and tracing published scientific works related to the theme of this study. After that, the writer analyzed the data and described it through analytical techniques using several stages, namely reducing data, classifying, and verifying data related to the study of this article. The results obtained in this paper have a significant level of using various features available in technology media to meet with teachers as described in this paper. Thus, the use of technology during the pandemic has a significant and influential role to be utilized by supervisors, teachers, and students.